Ethical Leadership and Employee Dynamics: A Study of Creativity and Turnover Intentions in the Manufacturing Industry of Pakistan - Nasir, Dr Aemin; Anum, Zarmeena; Traiq, Umair (UW Journal of Management Sciences, 2024)
Purpose: This study examined Ethical Leadership from the perspective of its two important aspects: creativity and Turnover Intention. This research provides one of the fundamental main truths in creating and maintaining a culture of creativity and reducing the increasing trend of Turnover Intention for every type of organization. Design and Methodology: This current study population frame include the manufacturing firms operating in Rahim Yar Khan. The study population are 1000 respondents from the manufacturing firms operating in the Rahim Yar Khan district. According to the Sekaran table, the sample was 440. A cross-sectional approach was used to collect data about ELEL, employee behavior (creativity & TOI), employee feelings (PCPC & voice), and leader moral conviction. SPSS was used for analysis. Findings: The findings showed that moral Leadership encourages employee creativity and revealed a significant link between employee innovation and moral Leadership. This study has also adequately shown how ethical Leadership affects employee innovation and found that ethical Leadership had a substantial impact on employees' intentions to quit their jobs. Implications: Ethical Leadership is essential to fostering a sense of dedication and involvement among workers at the workplace. The study contributes to our understanding of the factors influencing employee turnover intentions in Pakistan's manufacturing sector. Keywords: Ethical Leadership, Employee Creativity, and Turnover Intention,